The Role of the Dancer : The Effect a Dancer has on a Creative Process - Jóna Hlín Elíasdóttir 2000- (2022)
The role of the dancer is discussed in this essay regarding a creative process and how it can vary from being an individual and also a part of a group. The main subject is based on two pieces that were created for the graduating contemporary dance class of 2022 from the Iceland University of the Arts. The pieces were called Run/through by Katrín Gunnarsdóttir and Phygital Glitch by Gígja Jónsdóttir. The role of a dancer can vary from different processes, so the job of a dancer is forever changing. The author asks the question “What is the role of the dancer and what impact do they have on a creative process?” The main research is from a personal point of view from a dancer that experienced both processes. The aim of this research is to find out what challenges may intail in a creative process for the dancer and to see if the dancer generally has any input in this type of work. To get a good overview of how a creative process can be diverse it is also talked about the creative processes by other choreographers for example Siobhan Davies. In this essay it is discussed how significant the creative input from a dancer can be in a creative process and how important it is to be able to work by yourself and with a collective. In this essay it is discussed how important a good relationship between a dancer and their collective collaborators can be in a creative process.